Simulation Study of BACM Mold Respect to Temperature Distribution - Katimon, Mohd Nizam; Sapaat, Azri Izani (Research Progress in Mechanical and Manufacturing Engineering, 2021)
The Bladder Assisted Composite Manufacturing (BACM) technique is one of the method to produce hollow product. Mostly, issue in design, research and development effort are requirement to overcome the challenge in mold design. Another that, for selecting the bladder material, controlling the pressure and temperature of the heated air inside the bladder in BACM method is most important thing to make sure the successful of the process. In this work, the focus is to design the mold of BACM, starting with getting the accurate dimension of cylinder hollow of the final product. In addition, a good selection of material mold is essential to withstand the maximum processing temperature. This research requires the use of SolidWorks software to design mold of BACM, and it is easier to design the mold and the quality of the design can be improved. The analysis and simulation of the mold is representing in thermal analysis and pressure analysis. The process of simulation used 200 °C, 400 °C, and 600 °C temperature and 3 bar, 5 bar, 7 bar pressure in the studied. Since the operating system of BACM process of temperature between 100 °C to 250 °C, so the part is secure to use under 600 °C temperature because melting point of material about 600 °C. The simulation result for thermal analysis and pressure analysis shown the mold is secured.